JOB SATISFACTION AND CAREER CHOICES: A STUDY USING SCHEIN´S CAREER ANCHOR MODEL - Codaro, Rosana Silvina (2017)
This study explores the relationship between job satisfaction and alignment between the individual´s current occupation and his/her talents, needs and values, namely as career anchors. A quantitative survey using Schein e Van Maanen´s Career Anchor model (2013) and Siqueira´s Job Satisfaction survey (2008) was performed for a non-probabilistic sample students at the Business School of a private University in Rio de Janeiro. The most frequent career anchor found for both genders was Lifestyle, showing a trend towards finding a career that allows some balance between professional and personal life. Finally, we identified that autonomous individuals are more satisfied than those who receive salary, male ones are more satisfied with the job than the female ones, and there is a positive association with years of experience and satisfaction in the job.